Current Enlightenment About Etiology and Pharmacological Treatment of Autism Spectrum Disorder - Eissa, Nermin; Al-Houqani, Mohammed; Sadeq, Adel; Ojha, Shreesh K.; Sasse, Astrid; Sadek, Bassem (Frontiers in Neuroscience, 2018)
Autistic Spectrum Disorder (ASD) is a complex neurodevelopmental brain disorder is characterized by two core behavioural symptoms, namely impairments in social communication impairments and restricted/repetitive behaviour. The molecular mechanisms underlying ASD are not well understood. Recent, genetic as well as non-genetic animal models contribute in understanding the pathophysiology of ASD, as they establish autism-like behaviour in mice and rats. Among the genetic causes, several chromosomal mutations including duplications or deletions could be possible causative factors of ASD. In addition, the biochemical basis suggests that several brain neurotransmitters, e.g. dopamine (DA), systems including serotonin (5-HT), dopamine, gamma-amino butyric acid (GABA), acetylcholine (ACh), glutamate (Glu) and histamine (HA) participate in the onset and progression of ASD. Despite of convincible understanding, risperidone and aripiprazole are the only two drugs available clinically for improving behavioural symptoms of ASD following approval by Food and Drug Administration (FDA). Till date, up to our knowledge there is no other drug approved for clinical usage specifically for ASD symptoms. Many novel drug candidates and classes of compounds are underway for ASD at different phases of preclinical and clinical drug development. In this review, the diversity of numerous aetiological factors and the alterations in variety of neurotransmitter generation, release and function linked to ASD are discussed with focus on drugs currently used to manage neuropsychiatric symptoms related to ASD. The review also highlights the clinical development of drugs with emphasis on their pharmacological targets aiming at improving core symptoms in ASD.